UPAYA MENINGKATAKAN KINERJA GURU SEKOLAH DASAR SE- KECEMATAN PANTAI CERMIN - Desi Sijabat; Tarsicius Sunaryo (Jurnal Manajemen Pendidikan, 2018)
Behavior or action by teachers in primary schools can be used as a strategy to improve the performance of elementary school teachers in Pantai Cermin sub-district. This study aims to analyze the influence of work motivation and academic supervision on teaching performance of elementary school teachers in PaNtai Cermin sub-district. This study uses regression analysis tool. The sample in this study were 35 teachers from 100 teachers using simple random sampling technique. The results showed that work motivation and academic supervision affect teacher performance can be described with the equation y = 0.42 + 0.44X1 + 0.43X2. Work motivation and academic supervision together can explain teacher performance by 51%. Efforts to improve teachers‟ performance include providing equal opportunities for teachers to attend training, improving payroll systems and increasing teachers' salaries according to regional minimum wages, building close relationships among teachers and principals and cultivating deliberations in the school environment and continuous guidance